Caminhante: espaço urbano, espaço digital e suas relações - Roberta Ribeiro Hentschke (2012)
The present study aims to discuss the urban space and its relationship with the digital space in order to boost its valorization and appropriation. The relationship between the citizens and the city through the walking aimlessly, the search of meanings and the construction of new landscapes is reported here using the approach and the use of the digital space as a promoter and incentive of new territorialisation. It starts with the premise that there was an abandonment of urban space by people in lasts decades due to the advancement of technologies and urbanism strategies that do not prioritize the citizen. Having as a sitio the historicalcentre of Porto Alegre, Rio Grande do Sul, Brazil, an overview of projects and actions that had as an aim recover or claiming aspects of urban space is made in order to, finally, present a contemporary flaneur proposal, a wander through the city looking for an own point of view. In this case, with a bias towards art, design and architecture, combining the offline with the online, discussing its possibilities of participation and updating. Furthermore, the study intends to establish new perspectives on the urban space, providing new pathways, meshing territories andvaluing place, the location. It is not intended to present a solution to solve any issues related to the use of urban spaces, but a solution to start a conversation, to encourage, to see how possible it is to create a culture of urban space appreciation.